2017
DOI: 10.1097/icl.0000000000000240
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Perceptions of Patients Wearing Decorative Contact Lenses Purchased Through Unauthorized Sellers

Abstract: A significant number of individuals who obtain contact lenses illegally from unauthorized sources are young adults. Most unauthorized sellers reviewed did not adhere to the proper protocol for selling contact lenses or instruct their customers on proper lens wear and care. A significant percentage of optometrists responding to the survey reported complications associated with contact lenses purchased through unauthorized sources, suggesting that the risk of contact lens-related complications increases when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
5
0
2
Order By: Relevance
“…In contrast, Australasian practitioners were very sceptical about this opportunity (Median: 2/10), confirming that these types of CLs are appreciated depending on the geographical region, population demographics and the culture as reported earlier [58]. Noticeably, practitioners in North America (Median: 4/10) reported cosmetic CLs are more connected to non-legal purchase, in particular via online sources, and as linked to the development of CL-related complication, despite the FDA and professional bodies regulating this type of CLs [59].…”
Section: Opportunitiessupporting
confidence: 58%
“…In contrast, Australasian practitioners were very sceptical about this opportunity (Median: 2/10), confirming that these types of CLs are appreciated depending on the geographical region, population demographics and the culture as reported earlier [58]. Noticeably, practitioners in North America (Median: 4/10) reported cosmetic CLs are more connected to non-legal purchase, in particular via online sources, and as linked to the development of CL-related complication, despite the FDA and professional bodies regulating this type of CLs [59].…”
Section: Opportunitiessupporting
confidence: 58%
“…[5,[21][22][23] In addition, Gaiser et al reported that most people who obtain contact lenses from unauthorized sources are young adults, and suggested that the risk of contact lensrelated complications increases when the lenses are purchased from these sources. [24] Their results further support the argument that the purchase of contact lenses without a prescription poses a serious threat to the health and safety of consumers. However, all of our participants were under the supervision of eye care professionals and received the necessary training and support for correct insertion, removal and cleaning of their lenses, which is frequently not the case for over-the-counter customers.…”
Section: Discussionmentioning
confidence: 53%
“…Surveys indicate frequent online (24%) purchase or borrowing/obtaining (18%) from friends and family. 58 In this survey, most unauthorized sellers reviewed did not adhere to the proper protocol for selling contact lenses or instruct their customers on proper lens wear and care. 58 This might predispose the users to contact lens–related complications.…”
Section: Decorative Contact Lensesmentioning
confidence: 99%